PELAKSANAAN PERJANJIAN BANK GARANSI OLEH BANK NAGARI CABANG UTAMA KOTA PADANG DENGAN CV. FEBRIANO MITRA LESTARI TERKAIT WANPRESTASI ATAS PEMBANGUNAN GEDUNG PELAYANAN PERPUSTAKAAN DI KABUPATEN DHAMASRAYA - Haniva Rahmadani; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The word warranty comes from the Dutch language, Garantie which means guarantee. Bank guarantee is a guarantee given by the Bank, in the sense that the bank declares a written acknowledgment whose contents agree to bind itself to the recipient of the guarantee within a certain period of time and certain conditions if in the future it turns out that the assured does not fulfill his obligations to the recipient of the guarantee. Implementation of the work may arise defaults carried out by the parties to the agreement. In such circumstances, the provisions which must be fulfilled that arise due to default, namely the possibility of termination of the agreement, compensation or fulfillmentThe purpose of writing this thesis, namely: first, to find out the implementation of the bank guarantee agreement by Bank Nagari with CV. Febriano Sustainable Partners, second, to find out the efforts to resolve defaults made by CV. Febriano Mitra Lestari.This type of research belongs to the type of Sociological Juridical research. According to Sutrisno Hadi, Sociological Juridical research is an effort to determine, develop, and test the truth of knowledge. Efforts are made using scientific methods for the research. This research was conducted and to complete the data source, the authors conducted research on the CV. Febriano Mitra Lestari located in Padang City, the data used are primary data, secondary data and data collection techniques in the form of research with interviews.From the results of this study it can be concluded that, First, To get a Bank Guarantee from Bank Nagari Main Branch Padang, CV first. Febriano Mitra Lestari submits an application in the form of a Bank Guarantee Application Submission Letter to the Nagari Bank of Padang Main Branch with a reply letter of approval from the Bank in the form of a Bank Guarantee Approval Letter (SPPBG) to CV. Febriano Mitra Lestari. Second, the implementation of the Bank Guarantee agreement by Bank Nagari Padang Main Branch with CV. Febriano Mitra Lestari can be carried out with the applicable provisions stipulated by Bank Nagari Padang Main Branch. Third, efforts to settle the defaults carried out by CV.Keywords: Bank Guarantee-Default